BIOARANG LIMBAH DAUN KETAPANG (Terminalia catappa L.) SEBAGAI ADSORBEN ZAT WARNA METILEN BIRU DALAM LARUTAN BERAIR - Asnifa Yully; Muhdarina '; Nurhayati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Terminalia catappa leaves waste is a biomass waste that can be found around campus of Riau University. After carbonization at various time at temperature of 300 ˚C, biocharcoal of Terminalia catappa leaves waste was used for the adsorption of methylene blue from aqueous solution. Parameters of contact time and concentration of the adsorbate were varied in order to determine the adsorption capacity. Water and ash content of biocharcoal of Terminalia catappa leaves waste were also identified. The results showed that the adsorption methylene blue each of biocharcoal was 4,3478; 6,0024 and 5,1281 mg/g at the carbonization time 30, 60 and 120 minutes respectively, with the initial concentration of 40 ppm and the adsorption time is 15 minutes. Water content of biocharcoal of Terminalia catappa leaves with carbonization time of 30 minutes, 60 minutes and 120 minutes was 2,74%; 2,84% and 1 ,67% respectively, while the ash content was 14%; 13% and 15% respectively.